(untitled) (SAARC Journal of Agriculture, 2017)
This study evaluatesthe socio-economic demographic, as well as the preferences and behavioral characteristics of consumers who participate in bed and breakfast agritourism activity. The results from the logit model indicate that those who consumed a wider variety of fruits in the past 5 years, those who learn about agritourism from sign at market, those who consider that the facility at agritourism sites are important, those who have children under the age of 17, those who are retired from the job, and whose income range between 60,000 to 79,000 are more likely to be willing to participate in the bed and breakfast agritourism activity. However, those who learn about agritourism from newspapers, those who have two year collage education, male, homemakers, and whose income range from 20, 000 to 39,000 are less likely to be participate in bed and breakfast agritourism activity in Mid-Atlantic Region. SAARC J. Agri., 14(2): 162-173 (2016)